Comparison and clinical validation of qPCR assays targeting Leishmania 18S rDNA and HSP70 genes in patients with American Tegumentary Leishmaniasis. - Camila Patricio Braga Filgueira; Otacilio Cruz Moreira; Lilian Motta Cantanhêde; Heloísa Martins Teixeira de Farias; Renato Porrozzi; Constança Britto; Mariana Côrtes Boité; Elisa Cupolillo (Public Library of Science (PLoS), 2020)
Leishmaniasis is a worldwide neglected disease, encompassing asymptomatic infections and different clinical forms, such as American Tegumentary Leishmaniasis (ATL) which is part of the complex of diseases caused by protozoan parasites from Leishmania genus, transmitted by sand fly vectors. As a neglected disease, much effort is still needed in treatment and diagnosis. Currently, ATL diagnosis is mainly made by parasite detection by microscopy. The sensitivity of the method varies, and factors such as collection procedures interfere. Molecular approaches, specially based on Real Time PCR (qPCR) technique, has been widely used to detect Leishmania infection and to quantify parasite load, once it is a simple, rapid and sensitive methodology, capable to detect low parasite concentrations and less prone to variability. Although many studies have been already published addressing the use of this technique, an improvement on these methodologies, including an analytical validation, standardization and data association is demanded. Moreover, a proper validation by the assay by the use of clinical samples is still required. In this sense, the purpose of the present work is to compare the performance of qPCR using two commonly used targets (18S rDNA and HSP70) with an internal control (RNAse P) in multiplex reactions. Additionally, we validated reactions by assaying 88 samples from patients presenting different clinical forms of leishmaniasis (cutaneous, mucosal, recent and old lesions), representing the diversity found in Brazil's Amazon Region. Following the methodology proposed herein, the results indicate the use of both qPCR assays, 18S rDNA and HSP70, to achieve a very good net sensitivity (98.5%) and specificity (100%), performing simultaneous or sequential testing, respectively. With this approach, our main goal is to conclude the first step of a further multicenter study to propose the standardization of detection and quantification of Leishmania.